Alignment between Desires and Outcomes among Women Wanting to Avoid Pregnancy: A Global Comparative Study of "Conditional" Unintended Pregnancy Rates. Issue 1 (22nd February 2023) - Bearak, Jonathan Marc; Alkema, Leontine; Kantorová, Vladimíra; Casterline, John
Abstract: Since childbearing desires, and trends in these desires, differ across populations, the inclusion of women who want to become pregnant in the denominator for unintended pregnancy rates complicates interpretation of intercountry differences and trends over time. To address this limitation, we propose a rate that is the ratio of the number of unintended pregnancies to the number of women wanting to avoid pregnancy; we term these conditional rates. We computed conditional unintended pregnancy rates for five‐year periods from 1990 to 2019. In 2015–2019, these conditional rates per 1, 000 women per year wanting to avoid pregnancy ranged from 35 in Western Europe to 258 in Middle Africa. Rates with all women of reproductive age in the denominator have concealed stark global disparities in the ability of women to avoid unintended pregnancies, and they have understated progress in regions where the fraction of women wanting to avoid pregnancy has increased.